From Periphery to Core: Economic Adjustments to High Speed Rail - Arne Feddersen; Gabriel Ahlfeldt (European Regional Science Association (ERSA), 2011)
This paper presents evidence that high speed rail systems, by bringing economic agents closer together, sustainably promote economic activity within regions that enjoy an increase in accessibility. Our results on the one hand confirm expectations that have led to huge public investments into high speed rail all over the world. On the other hand, they confirm theoretical predictions arising from a consolidate body of (New) Economic Geography literature taking a positive, man-made and reproducible shock as a case in point. We argue that the economic geography framework can help to derive ex ante predictions on the economic impact of transport projects. The subject case is the German high speed rail track connecting Cologne and Frankfurt, which, as we argue, provides exogenous variation in access to regions due to the construction of intermediate stations in the towns of Limburg and Montabaur.
Keywords: 330